2023
DOI: 10.3390/jpm13010115
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Clinicopathological and Molecular Features to Predict Anti-PD-1-Based Therapy Efficacy in Patients with Advanced Gastric Signet Ring Cell Carcinoma

Abstract: Background: Signet ring cell carcinoma (SRCC) is a specific type of gastric cancer. The clinicopathological and molecular characteristics that can be used to predict the response to anti-PD-1 therapy for these patients are still not clear. Methods: Patients with advanced SRCC who received first-line anti-PD-1-based treatment were enrolled in this study. The clinicopathological characteristics of these patients were obtained from their medical records. The molecular features of these patients were analyzed by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
0
0
Order By: Relevance
“…The low sub-nanomolar K d value associated with avelumab suggests that [ 89 Zr]Zr-DFO-avelumab can detect lower concentrations of PD-L1 compared to [ 89 Zr]Zr-DFO-atezolizumab. This difference in K d values aligns with previous research findings, which reported a 5-fold increase in the K d value for radiolabeled atezolizumab when compared to avelumab ( 7 , 28 , 34 ). The superior binding affinity of avelumab may explain its enhanced uptake in our preclinical models of gastric cancer.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The low sub-nanomolar K d value associated with avelumab suggests that [ 89 Zr]Zr-DFO-avelumab can detect lower concentrations of PD-L1 compared to [ 89 Zr]Zr-DFO-atezolizumab. This difference in K d values aligns with previous research findings, which reported a 5-fold increase in the K d value for radiolabeled atezolizumab when compared to avelumab ( 7 , 28 , 34 ). The superior binding affinity of avelumab may explain its enhanced uptake in our preclinical models of gastric cancer.…”
Section: Discussionsupporting
confidence: 91%
“…Several biomarkers, ranging from tumor mutation burden and PD-L1 expression to microsatellite instability and Epstein–Barr virus infection status, have been proposed as potential indicators for identifying susceptibility to PD-1/PD-L1 inhibitors in gastric cancer ( 7 , 8 ). However, the outcomes of several clinical trials utilizing these biomarkers at an individual level exhibit inconsistency and, in some instances, even contradiction ( 9 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…The low sub-nanomolar K d value associated with avelumab suggests that [ 89 Zr]Zr-DFO-avelumab can detect lower concentrations of PD-L1 compared to [ 89 Zr]Zr-DFO-atezolizumab. This difference in K d values aligns with previous research findings, which reported a 5fold increase in the K d value for radiolabeled atezolizumab when compared to avelumab (7,28,34). The superior binding affinity of avelumab may explain its enhanced uptake in our preclinical models of gastric cancer.…”
Section: Discussionsupporting
confidence: 90%
“…Several biomarkers, ranging from tumor mutation burden and PD-L1 expression to microsatellite instability and Epstein-Barr virus infection status, have been proposed as potential indicators for identifying susceptibility to PD-1/PD-L1 inhibitors in gastric cancer (7,8). However, the outcomes of several clinical trials utilizing these biomarkers at an individual level exhibit inconsistency and, in some instances, even contradiction (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%